(untitled) (The Strategic Review for Southern Africa, 2020)
Given the urgency of redressing South Africa’s unjust legacies of the past, we interrogate the nature of support and opposition to restitution in South Africa. Informed by responses to the nationally representative South African Social Attitudes Survey (SASAS), we contend that South Africa remains deeply polarised when it comes to addressing these unjust legacies, with race being the major fault line. When it comes to restitution, South Africans are worlds apart on three levels. We are worlds apart across racial groups; we are worlds apart within racial groups, and we are worlds apart in the kind of language we wish to use in framing our pursuit of equality. In the final analysis, while South Africans may be unified in the acknowledgement that the inequality gap is too high, and perhaps even unified in a desire for change, there is a fundamental disagreement about the desirable vehicles we hope to employ.